Meningkatkan Minat Membaca Pada Anak Usia Sekolah Dasar Melalui Program Tayangan Televisi Dalam Perspektif Sosiologi - Bakhtiyar, Bakhtiyar; Hidayah, Imas Rahmadhtul (Fakultas Bahasa dan Sains, Universitas Wijaya Kusuma Surabaya, 2020)
The study aims to describe (1). The role of parents fostering interest in reading elementary school age children through television programs. (2). The positive impact of the TV program